Volatility of Islamic stock market and exchange rate: Granger causality and GARCH Approach - Mubarok, Faizul (Journal of Innovation in Business and Economics, 2023)
This research aims to investigate the causal relationship between the Islamic stock market and the exchange rate, as well as examine the volatility of the Islamic stock index in emerging countries. The study utilized the Granger causality test to analyze the causality between the Islamic stock market and the exchange rate and employed the Generalized Autoregressive Conditional Heteroscedasticity (GARCH) model for volatility analysis and forecasting. For this research, daily time series data ranging from 2012 to 2022 from the Islamic stock indices of Malaysia, Turkey, India, Pakistan, Indonesia, and Kuwait were selected as the sample. It was observed that the stock index had an impact on the exchange rate in Malaysia, Pakistan, India, and Turkey. Conversely, the exchange rate influenced the stock index in Indonesia, Kuwait, and Turkey.